2008
DOI: 10.2337/db07-0910
|View full text |Cite
|
Sign up to set email alerts
|

Low Physical Activity Accentuates the Effect of the FTO rs9939609 Polymorphism on Body Fat Accumulation

Abstract: OBJECTIVE-Three independent studies have shown that variation in the fat mass and obesity-associated (FTO) gene associates with BMI and obesity. In the present study, the effect of FTO variation on metabolic traits including obesity, type 2 diabetes, and related quantitative phenotypes was examined. RESEARCH DESIGN AND METHODS-The FTO rs9939609 polymorphism was genotyped in a total of 17,508 Danes from five different study groups.RESULTS-In studies of 3,856 type 2 diabetic case subjects and 4,861 normal glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
387
5
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(437 citation statements)
references
References 17 publications
36
387
5
9
Order By: Relevance
“…There is also evidence suggesting a modifying effect of physical activity on specific genes; a Danish study found that the rs9939609 polymorphism of the FTO gene is associated with greater BMI in sedentary persons than in physically active persons. 62 Similar results have also been reported in an Amish population. 63 The studies were cross-sectional in design and the findings therefore need confirmation in prospective studies, excluding an effect of development of obesity on physical activity.…”
Section: Possible Sources Of Bias In Adoption Studiessupporting
confidence: 77%
“…There is also evidence suggesting a modifying effect of physical activity on specific genes; a Danish study found that the rs9939609 polymorphism of the FTO gene is associated with greater BMI in sedentary persons than in physically active persons. 62 Similar results have also been reported in an Amish population. 63 The studies were cross-sectional in design and the findings therefore need confirmation in prospective studies, excluding an effect of development of obesity on physical activity.…”
Section: Possible Sources Of Bias In Adoption Studiessupporting
confidence: 77%
“…Thus, this FTO gene variant associates with other phenotypes when compared with previously studied FTO variants where the associations are almost exclusively mediated by differences in BMI. 6,8,9 The FTO gene encodes a probable 2-oxoglutarate-dependent nucleic acid demethylase 19 and is expressed in multiple peripheral and central tissues, 3,20 which is characteristic for a gene that may display a pleiotropic character influencing several systems simultaneously. This suggests that FTO and polymorphism, such as c.896 þ 223A4G and rs9939609, that are not in linkage disequilibrium with each other may have different molecular effects on metabolic conditions and phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Increased BMI levels and risk of obesity for FTO variants have been replicated in several cohorts consisting of adults 5 as well as adults and children. 3,4,6,7 Associations between FTO variants and metabolic traits such as fasting insulin, glucose, cholesterol and triglycerides have also been found. These associations were, however, abolished when adjusting for BMI.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most extensively studied example of a gene interaction with physical activity in obesity is for the FTO locus, concluding in general that physical inactivity accentuates the association of FTO variants with obesity-related traits (Andreasen et al, 2008;Rampersaud et al, 2008;Lee et al, 2010;Ruiz et al, 2010;Xi et al, 2011). However, this gene versus physical activity interaction in obesity was not yet assessed in a young adult population.…”
Section: Introductionmentioning
confidence: 99%